Phylogeographic structure in the CFR genus Pauridia revealed by inter-simple sequence repeat amplification - Burman, Marc (Department of Biological Sciences, 2017)
The Cape Floristic Region, South Africa, has high numbers of rare and endemic plants. Many, including Pauridia Harv., are geophytes in the Hypoxidaceae. The two species of Pauridia differ in morphology and range, with P. minuta occupying a wide range across lowland CFR and P. longituba being restricted to granite outcrops on the West coast. Genetic structure correlated to geography has been described for the haploid chloroplast genome. Here the diploid nuclear genome is investigated using inter-simple sequence repeat amplification. Eleven populations were sampled from DNA collected for a previous study. Analysis of molecular variance was done. Ordination based on similarity and covariance was done to detect structure. Most of the variance was found to be within populations (65.54%) and between populations within groups (35.69%). Some variance (10.10%) was found between P. minuta geographic groups. Principal Component Analysis revealed a little structure, grouping some similar haplotypes together. Cluster analysis placed P. longituba within P. minuta, reflecting the haplotypic structure. Differences in structure revealed between the chloroplast and nuclear genome may be explained by differences in gene flow resulting from the different modes of inheritance - chloroplast via seed and nuclear via pollen and seed. Further analysis of genetic distance correlations between the chloroplast and nuclear data would provide a useful quantitative measure of difference in structure.